Estudio de factibilidad para la creación de una aplicación móvil para el seguimiento estudiantil académico y disciplinario de los alumnos de la Unidad Educativa 8 de Noviembre de la Parroquia Balsapamba del cantón San Miguel Provincia Bolívar - Angamarca Naranjo, Katherin Natividad (2021)
In the actuality, mobile applications are an important complement to smartphones since they allow users to carry out different activities simply and instantly, especially efficient effective communication channels between different institutions, communities and people from all parts of the world. This research work consists of the Feasibility study for the creation of a mobile application for the academic and disciplinary student follow-up of the students of the "Educational Unit November 8" of the Balsapamba parish, San Miguel, Bolívar province. Due to the fact that the institution presents problems in the manual part, the records are lost, which makes correct follow-up difficult. In addition, each school year a new tutor is assigned to each parallel and in turn a new record of observations of each student is started. This leads to not knowing if the student's performance is regressive or progressive. In addition, the reports that are delivered to the parents of their respective representatives are not very detailed and difficult to understand, due to the number of students by parallels that are handled and the additional tasks that each tutor must fulfill with the Educational Institution. The methodology used is that of the field together with two methods that are: The qualitative one with the interview technique and the questionnaire instrument; and the quantitative one with its respective survey technique. What helped us to determine the current situation and the existing problem, to provide an efficient solution through the mobile application, which will guarantee a correct control and monitoring of the students, improving the teaching-learning process and guaranteeing an education with warmth and quality.